Virtue Ethics and its Place in Ethical Theory - Buganza, Jacob (Estudios de Filosofía, 2017)
In this article, the author seeks to show how the virtue ethics is framed in an “ethical theory”, so it is not necessary to complete it with an external ethical theory, as pragmatism, emotivism or criticism. Virtue ethics has an ethical theory that becomes consistent, and proof of this is the moral philosophy of Rosmini, which may fall within the classical tradition of moral philosophy.